Kawasan Pabrik dan Dampak Lingkungan Kotamadya Bitung - Langingi, Julius (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
Enviromental study was considered significant to the growing industrial zone of Bitung as the city started to implement KABINA industrial project. The enviroment analysis is also related to the preparation of the growing city as a port site as stated by the community representative committe for Bitung to be the city for container port in the Pacific rim and to boast economy and trade activities for Bitung as well as to grow economi rate for the Northern Sulawesi Province. This research is intended to specifically study the effect of manufacturing industrial waste disposal to its surrounding communities in Bitung. Further more the study intends to point out the importance of enviroment conservations and the effect of offective industrial waste recycling for the benefit of the community. The enviroment phenomenon towards community income, their life style, and personal rights. The second enviroment phenomenon used the factors of polotical and cultural situation as well as investment climate as its basis. Effective recyling of living and growing economics of the surrounding communities in the city of Bitung.